Subject vs. functional: Should subject librarians be replaced by functional specialists in academic libraries? - Hoodless, Catherine; Pinfield, Stephen (Journal of librarianship and information science, 2018)
This paper focuses on the move by some academic libraries to replace subject-based organisational structures with new functional structures, introducing functional specialists instead of subject librarians. It reports 11 in-depth semi-structured interviews with senior managers in UK libraries discussing their attitudes to this change. Key drivers for change included the desire to align the library more closely with institutional strategy and provide enhanced research support. However, there were also major concerns, particularly the loss of close relationships with academic departments. Little consensus emerged apart from agreement that this is a major current debate impacting significantly on the future positioning of libraries in their institutions.